Dropout rate of anti-rabies vaccination among rural and urban communities in Tamil Nadu: A comparative cross-sectional study - Vinodhraja Sellan; Karthik Recharla Chenchu; Vikram Ashokkumar; Ezhilvanan Mani (Asian Journal of Medical Sciences, 2023)
Background: Rabies is a vaccine preventable deadly disease. There is a lack of organized surveillance system on animal bite victims to ensure completion of full course of post-exposure prophylaxis. Aims and Objectives: The aim of the study was to estimate the dropout rate of anti-rabies vaccine (ARV) post-exposure regimen among rural and urban communities of Chengalpattu district, Tamil Nadu. To interpret the association between category of bite and vaccination outcome among rural and urban communities of Chengalpattu district, Tamil Nadu. Materials and Methods: A retrospective hospital record based study (ARV REGISTER) was done in urban primary health center (PHC) Haridosspuram and rural PHC, Kelambakkam during January 2021. Collected data were entered into MS Excel and analyzed using SPSS version 22.0. Total dropout rates of ARV regimen among rural and urban communities were compared by Chi-square test. Results: A total of 5262 animal bite victims were vaccinated during the past 2 years. The majority (37.4%) of victims belonged to 21–40 years of age. The total dropout rate observed among both rural and urban communities was 51.2% with the higher proportion (72.8%) of dropouts seen among victims of category I bite. Wound washing practice was observed among the victims. Higher dropout rate (61.3%) of ARV regimen was observed among urban communities compared to rural communities (50.2%). Significant association was found between the category of animal bite and the vaccination outcome in both rural and urban communities. Conclusion: The animal bite victims should be educated and counseled about the importance of complete vaccination. The health workers should ensure proper follow-up of the victims to complete the vaccination schedule and thus prevent drop outs.